Microstrip-Fed Circular Disc Monopole Antenna with Defected Waveguide Structure - S. J. Chin; M. Z. A. Abd. Aziz; M. R. Ahmad (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper presented the microstrip-fed circular disc monopole antenna with defected waveguide structure. First, the microstrip-fed circular disc monopole antenna was designed. Next, the monopole antenna was designed with waveguide and lastly followed by the defected waveguide structure where the uniplanar compact (UC) structure was used. CST Microwave studio software was used for simulation and parametric studies process. Initially, the microstrip-fed circular disc monopole antenna was designed to achieve return loss less than -10dB for wideband frequencies. Then, the gain and directivity was improved with the integration of waveguide. The highest directivity of 11.38dBi found at 13.5GHz. However, low efficiency and narrower bandwidth were obtained. Next, uniplanar compact defected waveguide structure (UC DWS) was designed at inner surface of waveguide. The bandwidth achieved 3.09GHz where it covered from 10.91GHz to 14GHz. Meanwhile, the directivity maintained higher than the monopole antenna with highest directivity of 8.84dBi at 10GHz. The gain was also improved from 11GHz to 14GHz with highest gain of 6.38dB occurred at 13.5GHz.